Pregnancy outcome and delivery in Spanish and migrant women: an ecological approach - Bernis, Cristina; Varea, Carlos (Anthropological Review, 2013)
For most of our history as a species, maternal constraint was the main environmental factor affecting biological status at birth. However, the great increase in medical intervention in the20th Century coincided first with an extraordinary reduction in perinatal mortality and later with an increase in preterm and low birth-weight babies. Herein, we analyze these temporary trends in neonate biology in Spain, according to early viability (1980–2010) and ethnic variability (1996–2010). The aim of this study is to evaluate the interaction between maternal and medical environmental constraints affecting the biology of birth and to understand the observed ethnic differences and secular trends. All single births in Spain between 1980 and 2010 are included. Following descriptive analysis, logistic regression analysis was applied to evaluate the effect of secular trends, mode of delivery and mother’s origin on birth outcome after adjustment for other maternal bio-cultural factors. Results highlighted that mean birth weight decreased and prematurity increased in still births, live births and deaths before one day. In regard to ethnic differences, while there were no secular trends in weight by gestational age in the Spanish newborns, there was an increase among the newborns of foreign mothers. Spanish mothers experienced an increasing and higher frequency of low birth weight, while foreigners had an increasing and higher frequency of prematurity. Both groups, however, shared temporal reduction in gestational age, and although this was less marked in foreigners, it suggests a common trend related to medical care and increasing obstetric interventions.